Preparation method of phosphoric acid modified charcoal loaded nano zero-valent iron material and material
By making cotton straw into biochar and loading nano zero-valent iron with phosphoric acid modification treatment, phosphoric acid modified biochar is prepared to produce nano zero-valent iron material, which solves the problem of the existing biochar's poor removal effect on hexavalent chromium (Cr(VI)), and achieves efficient adsorption and reduction, which promotes sustainable environmental development.
Patent Information
- Application Number
- CN202411778954.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-21
AI Technical Summary
The existing biochar has poor effect on removing hexavalent chromium (Cr(VI)), and the waste phosphoric acid solution has high cost of treatment and poor recycling applicability.
By making cotton straw into biochar and modifying it with phosphoric acid, the phosphoric acid modified biochar is prepared to be used to adsorb and reduce hexavalent chromium (Cr(VI)).
The adsorption and reduction capacity of hexavalent chromium (Cr(VI)) has been significantly improved, with a maximum adsorption amount of 103.53 mg g-1, which is more effective than phosphoric acid modified biochar materials, achieving environmental sustainable development.
Smart Images

Figure CN119660872A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental functional materials and biomass resource utilization, and in particular to a preparation method and material of a phosphoric acid-modified biochar-loaded nano zero-valent iron material. Background Art
[0002] Hexavalent chromium (Cr(VI)) is a highly oxidizing and highly toxic heavy metal pollutant with widespread and serious hazards, posing a major threat to the environment and human health. At present, hexavalent chromium (Cr(VI)) is widely used in industrial processes such as stainless steel manufacturing, chrome plating, leather tanning, and wood preservation. Due to its water solubility and high activity, when hexavalent chromium (Cr(VI)) waste is not properly treated, it will seep into the groundwater and enter the ecosystem. The valence state of chromium in aqueous solution mainly exists in trivalent and hexavalent states. Trivalent chromium (Cr(III)) is relatively stable and therefore less toxic, while hexavalent chromium (Cr(VI)) is a highly toxic substance, and its toxicity far exceeds that of trivalent chromium (Cr(III)).
[0003] Biochar is a porous material prepared by pyrolysis of biomass waste under anaerobic conditions. Biochar has a highly aromatic structure and can be used as a reducing agent. It has stable properties and strong adsorption capacity. Biochar can reduce the content of hexavalent chromium (Cr(VI)) in aqueous solution through adsorption and reduction. Therefore, biochar has long received widespread attention in environmental remediation.
[0004] Cotton straw, as an abundant agricultural waste, will cause serious environmental air pollution and resource waste whether it is buried or directly incinerated. It is worth noting that its low moisture, ash and high carbon content make it an effective and highly available biomass source for preparing biochar. Cotton straw has the advantages of low cost, easy access, pollution-free, large-scale preparation, and controllable structure and properties, and has broad application prospects.
[0005] Industries such as metal surface treatment produce a large amount of waste phosphoric acid (H3PO4) solution, which is far more harmful to the environment than industrial wastewater, has higher treatment costs and poor recycling applicability. Based on the concept of "waste treatment with waste", the reuse of waste cotton stalks makes biochar an environmentally sustainable option.
[0006] According to previous studies, it was found that the original biochar was not very effective in removing hexavalent chromium (Cr(VI)). Waste phosphoric acid (H3PO4) solution could be used to modify the biochar to improve its treatment performance.
[0007] The above problems are in urgent need of being solved. The present invention proposes a preparation method and material of a phosphoric acid-modified biochar loaded nano zero-valent iron material to solve the above problems. Summary of the invention
[0008] In this context, the present invention proposes a method for preparing a phosphoric acid-modified biochar-loaded nano-zero-valent iron material, wherein waste cotton straw is made into biochar, the biochar is modified using phosphoric acid, and nano-zero-valent iron is loaded on the modified biochar to obtain a phosphoric acid-modified biochar-loaded nano-zero-valent iron material, and waste cotton straw and phosphoric acid are used to adsorb and treat highly toxic hexavalent chromium (Cr(VI)).
[0009] In order to overcome at least one disadvantage of the prior art, on the one hand, the present invention provides a method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material, comprising the following steps:
[0010] S1: Cotton straw was washed, dried, ground, and then soaked in sodium hydroxide solution. Biochar was obtained after high-temperature pretreatment and named CS. NaOH ;
[0011] S2: Phosphoric acid (H3PO4) solution mixed with CS NaOH After drying, it is placed in a tube furnace for heating to obtain a black product, which is then mixed with hydrochloric acid (HCl) to obtain phosphoric acid-modified biochar, which is named PCS.
[0012] S3: Load zero-valent iron onto phosphoric acid-modified biochar to obtain phosphoric acid-modified biochar-loaded nano zero-valent iron material, which is named PCS@nZVI.
[0013] Preferably, the detailed steps of S1 are:
[0014] S1.1: washing the discarded cotton stalks, drying them, grinding and crushing them to obtain cotton stalk powder, and sieving the cotton stalk powder;
[0015] S1.2: taking the sieved cotton straw powder and immersing it in a sodium hydroxide solution (NaOH) to obtain a mixed solution, and subjecting the mixed solution to ultrasonic and oscillation treatment;
[0016] S1.3: Then place in a high temperature sterilizer for treatment;
[0017] S1.4: Wash with ultrapure water and dry to obtain CS NaOH .
[0018] Preferably, the drying in S1.1 is performed by heating at 105°C for 22-26h, and the sieve mesh is 100 mesh;
[0019] In S1.2, 10 g of cotton stalks and 1 L of 1.000 M sodium hydroxide solution (NaOH) were used, and the mixture was ultrasonically treated for 10 min and shaken for 30 min.
[0020] The high temperature sterilizer in S1.3 is set at 121°C and 15psi for 30 minutes;
[0021] The drying process in S1.4 is performed at 105° C. for 12 h.
[0022] Preferably, the detailed steps of S2 are:
[0023] S2.1: Take CS NaOH , phosphoric acid (H3PO4) solution to obtain a mixture;
[0024] S2.2: The mixture is subjected to ultrasonic shaking and then dried;
[0025] S2.3: Then place it in a tubular furnace in a nitrogen environment, uniformly heat it to 500°C, keep it at high temperature for 2 hours, cool it naturally to room temperature (25°C), and then take it out to obtain a black solid;
[0026] S2.4: Mix the black solid with hydrochloric acid (HCl) solution and shake for 30 min to remove ash;
[0027] S2.5: Then, the product is washed with ultrapure water and anhydrous ethanol and dried to obtain PCS modified with phosphoric acid.
[0028] Preferably, the S2.1 takes CS NaOH 3.600g, phosphoric acid (H3PO4) solution 9.036mL8.093M;
[0029] In S2.2, the ultrasonic treatment is performed for 10 minutes, the shaking treatment is performed for 12 hours, and the drying is performed at 80° C. for 12 hours;
[0030] In S2.3, the temperature was set at 10 °C min in a tube furnace. -1 Heating to 500°C;
[0031] The hydrochloric acid (HCl) solution in S2.4 is 1M, 10 g L-1;
[0032] The drying in S2.5 is performed at 105° C. for 12 h.
[0033] Preferably, the detailed steps of S3 are:
[0034] S3.1: Take ferrous sulfate heptahydrate (FeSO4·7H2O) solution, transfer it to a three-necked flask after ultrasonic treatment;
[0035] S3.2: Add PCS to a three-necked flask, introduce nitrogen, and stir magnetically;
[0036] S3.3: Slowly add sodium borohydride (NaBH4) solution to the solution in S3.2, react for 15 min under nitrogen (N2) environment, and centrifuge the solution to obtain a solid substance;
[0037] S3.4: The obtained solid was washed twice with anhydrous ethanol, dried, and fully ground to obtain PCS@nZVI.
[0038] Preferably, the ferrous sulfate heptahydrate (FeSO4·7H2O) solution in S3.1 is 200 mL 0.05 M and is ultrasonically treated for 20 min;
[0039] Add 0.5 g PCS to S3.1 and stir magnetically for 1 h;
[0040] In the step S3.3, the slow dripping speed is 10 mL / min, 20 mL of 10.77 g L-1 sodium borohydride (NaBH4) solution is added, the centrifugal speed is 8000 r / min, and the centrifugal time is 5 min;
[0041] The drying in S3.4 is performed under vacuum at 50° C. for 24 h.
[0042] On the other hand, the present invention provides a phosphoric acid-modified biochar-loaded nano-zero-valent iron material, which is prepared by the preparation method of a phosphoric acid-modified biochar-loaded nano-zero-valent iron material described in any one of the above items.
[0043] On the other hand, the present invention provides an application of a phosphoric acid-modified biochar-loaded nano-zero-valent iron material, and a device or process for adsorbing hexavalent chromium (Cr(VI)) using the above-mentioned phosphoric acid-modified biochar-loaded nano-zero-valent iron material.
[0044] The beneficial effects of the invention are:
[0045] 1. The present invention uses waste cotton straw to make biochar, and then modifies the biochar and loads nano zero-valent iron to obtain a phosphate-modified biochar loaded with nano zero-valent iron material.
[0046] 2. The phosphoric acid-modified biochar-loaded nano zero-valent iron material of the present invention can improve the adsorption and reduction of highly toxic hexavalent chromium (Cr(VI)), and adopts the idea of "treating waste with waste" to achieve environmental sustainable development.
[0047] 3. After being loaded with nano zero-valent iron, the present invention more effectively removes Cr(VI) than the phosphoric acid-modified biochar material. The maximum adsorption capacity of PCS@nZVI for Cr(VI) is 103.53 mg g-1, and the maximum adsorption capacity of PCS@nZVI for Cr(VI) is 1.5 times that of PCS. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The present invention is preferably described below in conjunction with the accompanying drawings and embodiments.
[0049] In the figure: Figure 1 is the SEM image of PCS;
[0050] Figure 2 is the SEM image of PCS@nZVI;
[0051] Figure 3 Nitrogen adsorption-desorption curves of PCS and PCS@nZVI;
[0052] Figure 4 is the pore size distribution diagram of PCS and PCS@nZVI;
[0053] Figure 5 XRD patterns of PCS and PCS@nZVI;
[0054] Figure 6 XRD and FT-IR spectra of PCS and PCS@nZVI;
[0055] Figure 7 The removal effect of hexavalent chromium Cr(VI) by PCS@nZVI at different concentrations;
[0056] Figure 8 The removal effect of PCS@nZVI on Cr(VI) at different dosages;
[0057] Fig. 9 is the removal effect of PCS on Cr(VI) at different pH;
[0058] Fig.10 The removal effect of PCS@nZVI on Cr(VI) at different pH values;
[0059] Fig.11 Kinetic fitting curves of PCS and PCS@nZVI;
[0060] Fig.12 Isotherm fitting curves of PCS and PCS@nZVI. DETAILED DESCRIPTION
[0061] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0062] The present invention provides a method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material, comprising the following steps:
[0063] S1: Cotton straw was washed, dried, ground, and then soaked in sodium hydroxide solution. Biochar was obtained after high-temperature pretreatment and named CS. NaOH .
[0064] S1.1: washing the discarded cotton stalks, drying them, grinding and crushing them to obtain cotton stalk powder, and sieving the cotton stalk powder;
[0065] S1.2: taking the sieved cotton straw powder and immersing it in a sodium hydroxide solution (NaOH) to obtain a mixed solution, and subjecting the mixed solution to ultrasonic and oscillation treatment;
[0066] S1.3: Then place in a high temperature sterilizer for treatment;
[0067] S1.4: Wash with ultrapure water and dry to obtain CS NaOH .
[0068] S2: Phosphoric acid (H3PO4) solution mixed with CS NaOH After that, it is dried and heated in a tube furnace to obtain a black product. The black product is mixed with hydrochloric acid (HCl) and modified to obtain phosphoric acid-modified biochar, which is named PCS.
[0069] S2.1: Take CS NaOH , phosphoric acid (H3PO4) solution to obtain a mixture;
[0070] S2.2: The mixture is subjected to ultrasonic shaking and then dried;
[0071] S2.3: Then place it in a tubular furnace in a nitrogen environment, uniformly heat it to 500°C, keep it at high temperature for 2 hours, cool it naturally to room temperature (25°C), and then take it out to obtain a black solid;
[0072] S2.4: Mix the black solid with hydrochloric acid (HCl) solution and shake for 30 min to remove ash;
[0073] S2.5: Then, the product is washed with ultrapure water and anhydrous ethanol and dried to obtain PCS modified with phosphoric acid.
[0074] S3: Load zero-valent iron onto phosphoric acid-modified biochar to obtain phosphoric acid-modified biochar-loaded nano zero-valent iron material, which is named PCS@nZVI.
[0075] S3.1: Take ferrous sulfate heptahydrate (FeSO4·7H2O) solution, transfer it to a three-necked flask after ultrasonic treatment;
[0076] S3.2: Add PCS to a three-necked flask, introduce nitrogen, and stir magnetically;
[0077] S3.3: Slowly add sodium borohydride (NaBH4) solution to the solution in S3.2, react for 15 min under nitrogen (N2) environment, and centrifuge the solution to obtain a solid substance;
[0078] S3.4: The obtained solid was washed twice with anhydrous ethanol, dried, and fully ground to obtain PCS@nZVI.
[0079] Example 1: Preparation of cotton straw biochar.
[0080] The discarded cotton straw was washed, dried at 105°C, and ground to obtain cotton straw powder. The cotton straw powder was sieved through a 100-mesh sieve, and 10 g of the sieved cotton straw powder was weighed and immersed in 1 L of 1.000 M NaOH solution to obtain a mixed solution. The mixed solution was ultrasonically treated for 10 min, shaken for 30 min, and then placed in a high-temperature sterilizer at 121°C and 15 psi for 30 min. After washing with ultrapure water, it was dried at 105°C for 12 h to obtain cotton straw biochar (CS NaOH ).
[0081] Specifically, the cotton straw in this embodiment comes from an agricultural waste factory in Lianyungang, China.
[0082] Example 2: Preparation of cotton straw biochar modified with phosphoric acid
[0083] Take 3.600g CS NaOH , 9.036 mL of 8.093 M phosphoric acid (H3PO4) solution to obtain a mixture, the mixture was ultrasonically treated for 10 min, shaken for 12 h, dried at 80 °C for 12 h, and then placed in a tube furnace in a nitrogen environment at 10 °C min -1 Heat to 500°C, maintain for 2 h, cool naturally to room temperature (25°C), and then take out the black solid. Take 1 M hydrochloric acid (HCl) solution (solid concentration is 10 g L -1 ) was mixed with the black solid and shaken for 30 min to remove the ash, followed by washing with ultrapure water and anhydrous ethanol and drying at 105 °C for 12 h to obtain cotton straw biochar (PCS) modified with phosphoric acid.
[0084] Example 3: Preparation of phosphoric acid-modified biochar loaded with nano zero-valent iron material
[0085] Take 200 mL of 0.05 M ferrous sulfate heptahydrate (FeSO4·7H2O) solution, transfer it to a three-necked flask after ultrasonic treatment for 20 min, add 0.5 g PCS to the three-necked flask, introduce nitrogen, magnetically stir for 1 h, slowly add 20 mL of 10.77 g L-1 sodium borohydride (NaBH4) solution to the solution, react for 15 min under a nitrogen (N2) environment to obtain a solid substance, wash the obtained solid twice with anhydrous ethanol, vacuum dry it at 50 ° C for 24 h, and grind it thoroughly to obtain phosphoric acid-modified biochar loaded nano zero-valent iron material (PCS@nZVI).
[0086] After carbonization, cotton straw contains rich pore structure and unique quasi-three-dimensional tubular structure with high nitrogen content, which improves the defect potential and electronic conductivity of hard carbon.
[0087] like Figure 1 , 2 As shown in the figure, the PCS surface presents a rough layered structure, which provides certain attachment sites for loading nano-zero-valent iron (nZVI). After loading nano-zero-valent iron (nZVI), PCS@nZVI presents irregular groove-shaped and chain-shaped pore structures, which increases the adsorption space of hexavalent chromium (Cr(VI)) to a certain extent and improves the adsorption performance of PCS@nZVI.
[0088] like Figure 3 As shown, the adsorption-desorption curve of PCS in nitrogen (N2) conforms to the IV type curve, and the hysteresis loop is determined to be the H4 type curve.
[0089] like Figure 4 As shown, the PCS material has a regular mesoporous structure, and the pore size is mainly distributed between 2-16 nm.
[0090] Table 1: Pore structure parameters of PCS and PCS@nZVI determined by BET method
[0091]
[0092] As shown in Table 1, the specific surface area of PCS is 401.64 m 2 ·g -1 After loading nano-zero-valent iron (nZVI), the surface area decreased to 395.08 m 2 ·g -1 This is because nano-zero-valent iron (nZVI) is distributed on the surface and in the gaps of PCS, reducing the specific surface area.
[0093] Nano-zero-valent iron (nZVI) has a large specific surface area, strong reducing ability and high reaction activity. Nano-zero-valent iron (nZVI) is unstable when exposed to the air, while the properties of biochar are stable. Loading it on modified biochar can not only solve the problem of nano-zero-valent iron (nZVI) being unstable when exposed to the air, but also ensure its stability and increase its reaction performance.
[0094] like Figure 5 As shown, peaks were observed between 2θ = 15°-30° for PCS and PCS@nZVI, which are attributed to amorphous carbon. Although the smaller peaks at 2θ = 23.4° and 43° correspond to graphitic carbon, the two diffraction peaks at 2θ = 44.29° and 64.38° can be considered as reflections of silicon carbide. This structural feature is characteristic of some carbonaceous substances, such as lignin and hemicellulose. Phosphoric acid (H3PO4) promotes amorphism and lattice defects in the carbon structure. The addition of phosphoric acid functional groups induced by phosphoric acid (H3PO4) impregnation and the presence of POP in the carbon lattice lead to carbon expansion and cross-linking. PCS@nZVI was found to have a peak around 43°, indicating the presence of nano zero-valent iron, indicating that PCS@nZVI has been successfully synthesized.
[0095] like Figure 6 As shown in the figure, the PCS and PCS@nZVI samples were analyzed by Fourier transform infrared spectroscopy, and the results showed that 3340 cm -1 and 1375cm -1 The broadband is related to the stretching vibration of -OH. After the nano-zero-valent iron is loaded, the characteristic peak becomes narrower. -1 and 1497cm -1 The peak at 629 cm indicates the presence of C=O and C=C functional groups on the biochar surface. -1 New Fe-O groups were observed at the sites, which was attributed to the loading of nano-zero-valent iron (nZVI), indicating the presence of nano-zero-valent iron (nZVI) in the PCS@nZVI composites.
[0096] like Figure 7 As shown in Figure 2, the removal rate of hexavalent chromium (Cr(VI)) gradually decreased with the increase of the initial hexavalent chromium (Cr(VI)) concentration. The initial concentrations were 20 and 50 mg L -1 When the concentration is increased to 100 mg L -1 When the concentration continues to increase, the removal rate can only reach about 37%, and when the concentration continues to increase, the removal rate begins to stabilize. Since the active sites of the adsorbent are fixed, when the pollutant concentration increases to a certain amount, the removal percentage will decrease. Hexavalent chromium (Cr(VI)) will passivate the zero-valent iron on the surface of the adsorbent and lose its activity, resulting in a decrease in removal efficiency.
[0097] like Figure 8 As shown, at a hexavalent chromium (Cr(VI)) concentration of 50 mg L -1 In the case of PCS@nZVI, the removal rate decreased with the increase of PCS@nZVI dosage. When the dosage increased from 0.1 g L-1 to 0.5 g L-1, the removal rate decreased with the increase of PCS@nZVI dosage. -1 The removal rate of hexavalent chromium (Cr(VI)) increased from 49% to 100%.
[0098] like Fig. 9 , 10 As shown, the removal effect of hexavalent chromium (Cr(VI)) at an initial pH of 3-11 is described. When the pH gradually increases, the effect of PCS@nZVI on the removal rate of hexavalent chromium (Cr(VI)) is smaller than that of PCS.
[0099] The adsorption process of hexavalent chromium (Cr(VI)) on the adsorbent was further studied by using the pseudo-first-order and pseudo-second-order models. Fig.11 As shown in the figure, the adsorption mechanism of PCS@nZVI for hexavalent chromium (Cr(VI)) is more consistent with chemical adsorption. The maximum adsorption capacity of PCS@nZVI for hexavalent chromium (Cr(VI)) is 103.53 mg g -1 , which is 1.5 times of PCS. Fig.12 As shown, it follows the Langmuir isotherm model, indicating its monolayer adsorption behavior.
[0100] The method for investigating the adsorption performance of simulated pollutants provided by the present invention is as follows:
[0101] Adsorption test operation steps:
[0102] In a 100 mL blue cap bottle, use 0.5 g L -1 The adsorption experiment of hexavalent chromium (Cr(VI)) by biochar was carried out in 50mL 50mg L-1 hexavalent chromium (Cr(VI)) solution. The pH value of the solution was adjusted using 0.1mol L-1 hydrochloric acid (HCl) and sodium hydroxide (NaOH). The mixture was shaken in the dark at 25°C and 150rpm for 240 min. 0.5mL of the collected liquid sample was filtered regularly using a 0.22μm filter, and the hexavalent chromium (Cr(VI)) concentration was determined by diphenylcarbazide spectrophotometry (GB 7467-87). In addition, the effect of initial pH value (3.0-11.0) on the adsorption of hexavalent chromium (Cr(VI)) by biochar was also studied.
[0103] Detection method of hexavalent chromium (Cr(VI)):
[0104] Potassium dichromate (purity 99%) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0105] In the experiment, all hexavalent chromium concentrations were determined by diphenylcarbazide spectrophotometry (GB 7467-87), and the spectrophotometry used a UV-vis spectrometer (UV2700, Japan) at a wavelength of 540 nm to measure the hexavalent chromium (Cr(VI)) concentrations of all samples.
[0106] The pseudo-first-order model and pseudo-second-order model were selected to fit the kinetic data of hexavalent chromium (Cr(VI)) removal.
[0107]
[0108] Qe and Qt (mg·g -1 ) are the amount of hexavalent chromium (Cr(VI)) adsorbed by the adsorbent at equilibrium time and time t; k1(min -1 )、k2(mg(g·min) –1 ) are pseudo-first-order and pseudo-second-order kinetic constants.
[0109] The adsorption data were then analyzed using the Langmuir and Freundlich models to predict heterogeneous adsorption.
[0110]
[0111] Where: C e (mg·g -1 ) is the concentration of hexavalent chromium (Cr(VI)) in the aqueous phase at equilibrium;
[0112] Q max (mg·g-1) and K F (L mg -1 ) are the Langmuir model constants, representing the maximum adsorption capacity and adsorption affinity between the adsorbent and the adsorbate, respectively;
[0113] K F (μ·g 1-1 / n ·L 1 / n ·g -1 )and n F is the Freundlich model constant.
[0114] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material, characterized in that: The following steps are involved: S1: Cotton straw was washed, dried, ground, and then soaked in sodium hydroxide solution. Biochar was obtained after high-temperature pretreatment and named CS. NaOH ; S2: Phosphoric acid (H3PO4) solution mixed with CS NaOH After drying, it is placed in a tube furnace for heating to obtain a black product, which is then mixed with hydrochloric acid (HCl) to obtain phosphoric acid-modified biochar, which is named PCS. S3: Load zero-valent iron onto phosphoric acid-modified biochar to obtain phosphoric acid-modified biochar-loaded nano zero-valent iron material, which is named PCS@nZVI.
2. The method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material according to claim 1, characterized in that: The detailed steps of S1 are: S1.1: washing the discarded cotton stalks, drying them, grinding and crushing them to obtain cotton stalk powder, and sieving the cotton stalk powder; S1.2: taking the sieved cotton straw powder and immersing it in a sodium hydroxide solution (NaOH) to obtain a mixed solution, and subjecting the mixed solution to ultrasonic and oscillation treatment; S1.3: Then place in a high temperature sterilizer for treatment; S1.4: Wash with ultrapure water and dry to obtain CS NaOH .
3. The method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material according to claim 2, characterized in that: The drying in S1.1 is performed by heating at 1105°C for 22-26h and the sieve mesh is 100 mesh; In S1.2, 10 g of cotton stalks and 1 L of 1.000 M sodium hydroxide solution (NaOH) were used, and the mixture was ultrasonically treated for 10 min and shaken for 30 min. The high temperature sterilizer in S1.3 is set at 121°C and 15psi for 30 minutes; The drying process in S1.4 is performed at 105° C. for 12 h.
4. The method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material according to claim 1, characterized in that: The detailed steps of S2 are: S2.1: Take CS NaOH , phosphoric acid (H3PO4) solution to obtain a mixture; S2.2: The mixture is subjected to ultrasonic shaking and then dried; S2.3: Then place it in a tubular furnace in a nitrogen environment, uniformly heat it to 500°C, maintain the high temperature for 2 hours, cool it naturally to room temperature (25°C), and then take it out to obtain a black solid; S2.4: Mix the black solid with hydrochloric acid (HCl) solution and shake for 30 min to remove ash; S2.5: Then, the product is washed with ultrapure water and anhydrous ethanol and dried to obtain PCS modified with phosphoric acid.
5. The method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material according to claim 4, characterized in that: The CS in S2.1 NaOH 3.600 g, phosphoric acid (H3PO4) solution 9.036 mL 8.093 M; In S2.2, the ultrasonic treatment is performed for 10 minutes, the shaking treatment is performed for 12 hours, and the drying is performed at 80° C. for 12 hours; In S2.3, the temperature was set at 10 °C min in a tube furnace. -1 Heating to 500°C; The hydrochloric acid (HCl) solution in S2.4 is 1M, 10 g L-1; The drying in S2.5 is performed at 105° C. for 12 h.
6. The method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material according to claim 1, characterized in that: The detailed steps of S3 are: S3.1: Take ferrous sulfate heptahydrate (FeSO4·7H2O) solution, transfer it to a three-necked flask after ultrasonic treatment; S3.2: Add PCS to a three-necked flask, introduce nitrogen, and stir magnetically; S3.3: Slowly add sodium borohydride (NaBH4) solution to the solution in S3.2, react for 15 min under nitrogen (N2) environment, and centrifuge the solution to obtain a solid substance; S3.4: The obtained solid was washed twice with anhydrous ethanol, dried, and fully ground to obtain PCS@nZVI.
7. The method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material according to claim 6, characterized in that: The ferrous sulfate heptahydrate (FeSO4·7H2O) solution in S3.1 is 200 mL 0.05 M and is ultrasonically treated for 20 min; Add 0.5 g PCS to S3.1 and stir magnetically for 1 h; In the step S3.3, the slow dripping speed is 10 mL / min, 20 mL of 10.77 g L-1 sodium borohydride (NaBH4) solution is added, the centrifugal speed is 8000 r / min, and the centrifugal time is 5 min; The drying in S3.4 is performed under vacuum at 50° C. for 24 h.
8. A phosphoric acid-modified biochar-loaded nano-zero-valent iron material, characterized in that: The material is prepared by the method for preparing a phosphoric acid-modified biochar-loaded nano zero-valent iron material as described in any one of claims 1 to 7.
9. An application of a phosphoric acid-modified biochar loaded with nano zero-valent iron material, characterized in that: A device or process for adsorbing hexavalent chromium (Cr(VI)) using a phosphoric acid-modified biochar-loaded nano-zero-valent iron material as described in claim 8.
Citation Information
Patent Citations
Advanced oxidation-alkali regulation precipitation combined method for treating EDTA-Cu wastewater
CN110627250A
Method for preparing biochar-loaded nano zero-valent iron by particle structure regulation and control strategy
CN113716545A
Preparation method and application of dual phosphorylated nano zero-valent iron with nano cracks
CN115475955A
Cited By
Soil improvement method for mangrove forest sapling planting
CN121647155A